Impact Of Lateral Separations Between Pit Latrines And Wells On Contamination Of Groundwater In The Tano Districts Of Ghana - F. Awuah; R.C. Abaido; K. Badu; S Appah (European Scientific Journal, ESJ, 2020)
The people in the Tano Districts of Ghana use groundwater as a source of drinking water and pit latrines for sanitation. However, when pit latrines and wells coexist, it is of paramount importance to ensure safer distances between them. This is to avoid faecal contamination of the groundwater. This study sought to investigate the impact of lateral separations between pit latrines and the wells on groundwater contamination in the Tano Districts of Ghana. To obtain a sample size of 15 wells within the proximity of pit latrines, a simple random sampling was considered in this study. It was revealed that none of the sites satisfied the Ministry of Water Resources, Works and Housing (MWRWH) of Ghana’s (2010) 50m guideline for lateral separation between a well and a pit latrine. It was also brought to light that there was not much variation of the lateral distances with the total and faecal coliform counts in the water. Even so, the enterococci counts seemed to have an inverse variation with the lateral separations between the pit latrines and the wells in this study area. The enterococci might be a better human faecal indicator than the other coliforms considered in this study. The study recommends strict enforcement of the MWRWH (2010) 50m guideline for lateral separation between a well and a pit latrine in the area studied. To investigate the human faeces as a contaminant, preference must be given to the enterococci as a faecal indicator than the other faecal determinants in this study.